Design and characterisation of a real time proton and carbon ion radiography system based on scintillating optical fibres. Issue 9 (September 2016) - Lo Presti, D.; Bonanno, D.L.; Longhitano, F.; Bongiovanni, D.G.; Russo, G.V.; Leonora, E.; Randazzo, N.; Reito, S.; Sipala, V.; Gallo, G.
Highlights: High resolution imaging: high spatial resolution (up to 150 μm), high resolution residual range measurement (up to 150 μm). Large sensitive area attainable (up to 40 × 40 cm 2 ). Smart read-out strategy for real time imaging and residual range measurement at high resolution. High rate beam compliance. Sensitive area realized by scintillating fibers, water equivalence. Abstract: This paper describes the design and characterization of a charged particle imaging system composed of a position sensitive detector and residual range detector. The position detector consists of two identical overlying and orthogonal planes each of which consists of two layers of pre-aligned and juxtaposed scintillating fibres. The 500 μm square section fibres are optically coupled to two Silicon Photomultiplier arrays using a channel reduction system patented by the Istituto Nazionale di Fisica Nucleare. The residual range detector consists of sixty parallel layers of the same fibres used in the position detector each of which is optically coupled to a Silicon Photomultiplier array by wavelength shifting fibres. The sensitive area of the two detectors is 9 × 9 cm 2 . Characterising the position sensitive and the residual range detectors to reconstruct the radiography, is fundamental to validating the detectors' designs. The proton radiography of a calibrated target in imaging conditions is presented. The spatial resolution of the position sensitive detector is about 150 μm and the range resolution is about 170 μm. The performance of the prototypes were tested at CATANA proton therapy facility (Laboratori Nazionali del Sud, INFN, Catania) with energy up to 58 MeV and rate of about 10 6 particles per second. The comparison between the simulations and measurements confirms the validity of this system.